1 3 3

:

  1. #1

    Jul 2012
    5,302

    :-
    6
    1/3 . .
    :-


    = 1 /3
    2 = 1/3 ( 4 ^2 )
    = 4/3 ^2 / 2
    = 2 /3 ( 6 ) = 4
    = 1
    1^2 = ( 6 )^2 - ( 2 )^2
    = 36 - 4 = 32
    1 = ( 32 ) = 4 2

    :-
    576 .
    :-
    4 ^2 = 576
    ^2 = 576 / 4 = 144
    = 12
    = 4/3 ^3
    = 4/3 ( 12 )^3
    = 2304

    :-
    6 12
    .
    :-
    = 4/ 3 ^3 = 4/3 3 3 3 = 36 ^3
    36 ^3


    = ^2
    36 = ( 12 )^2
    = 1/ 4







  2. #2

    Jul 2012
    5,302

    :

    :-
    = 100 ^2
    :-
    = 4 ^2
    = 100 = 4 ^2
    ^2 = 100 / 4 ............. ^2 = 25
    = 5
    = 4/ 3 ^3
    = 4/ 3 5 5 5
    = 4 125 / 3 = 500 / 3 ^3

    :-

    50
    :-

    = 4 ^2
    = 4 3.14 25 25
    = 100 3.14 25
    = 314 25 = 7850 ^2

    :-
    72 ^2 .

    :-
    = 72 ^2
    72 = 1/ 2 4 ^2

    ^2 = 72 / 2 = 36
    = 6

    :-
    6
    10
    :-

    1

    ( 10 )^2 = 1^2 + ( 4 )^2
    1^2 = 84

    = 2
    = 2 ( 10 ) ( 6 ) = 120 ^2
    = 1^2
    = ) 84 ) = 84 ^2

    = 120 + 84 = 204 ^2









  3. #3
      Eiman
    Jul 2011
    -
    14,750

    :

    .......

: 1 (0 1 )